Pharmacokinetics and Tissue Distribution of Aegeline after Oral Administration in Mice - Manda, Vamshi K.; Haron, Mona H.; Mir, Tahir M.; Avula, Bharathi; Ashfaq, Mohammad K.; Haider, Saqlain; Chittiboyina, Amar G.; Khan, Ikhlas A.; Khan, Shabana I. (Planta Medica, 2019)
Aegeline is claimed to be a biologically active constituent of Aegle marmelos. Preclinical studies have reported possible therapeutic potential for aegeline against obesity and diabetes. In recent years, aegeline has been added to several weight loss products. However, the consumption of aegeline-containing supplements such as OxyELITE Pro and VERSA-1 has been linked to multiple cases of acute and chronic liver failure. This study was carried out to evaluate the pharmacokinetics and tissue distribution of aegeline in ND4 mice. Two doses of aegeline, a human equivalent dose (1×) 30 mg/kg and a 10× dose (300 mg/kg), were orally administered to the mice, and blood and tissue samples were collected over 8 h. The quantitative analysis of plasma and tissue homogenates (liver, kidney, and brain) was done by UHPLC-QTOF to determine aegeline concentrations. The peak plasma level of aegeline was achieved at a Tmax of 0.5 h, indicating its rapid absorption from the gastrointestinal tract. Aegeline was not detected in the plasma at 8 h after oral administration, with a half-life of 1.4 ± 0.01 and 1.3 ± 0.07 h for the 30 and 300 mg/kg doses, respectively. The half-life of aegeline in the liver was 1.2 h and 1.7 h for 30 and 300 mg/kg doses, respectively, with a Tmax of 1.9 h, which indicates relatively fast elimination of aegeline from the liver.
Keywords: Aegeline; N-[2-Hydroxy-2(4-methoxyphenyl)ethyl]-3-phenyl-2-propenamide; Aegle marmelos; Rutaceae; pharmacokinetics